A risk-based framework for new products: a South African telecommunication's study - Jeffries, Michael (Rhodes University, Faculty of Science, Department of Computer Science, 2017)
The integrated reports of Vodacom, Telkom and MTN "” telecommunication organisations in South Africa "” show that they are diversifying their product offerings from traditional voice and data services. These organisations are including new offerings covering the financial, health, insurance and mobile education services. The potential exists for these organisations to launch products that are substandard and which either do not take into account customer needs or do not comply with current legislations or regulations. Most telecommunication organisations have a well-defined enterprise risk management program, to ensure compliance to King III, however risk management processes specifically for new products and services might be lacking. The responsibility usually resides with the product managers for the implementation of robust products; however they do not always have the correct skillset to ensure adherence to governance requirements and therefore might not be aware of which laws they might not be adhering to, or understand the customers' requirements. More complex products, additional competition, changes to technology and new business ventures have reinforced the need to manage risk on telecommunication products. Failure to take risk requirements into account could lead to potential fines, damage the organisation's reputation which could lead to customers churning from these service providers. This research analyses three periods of data captured from a mobile telecommunication organisation to assess the current status quo of risk management maturity within the organisation's product and service environment. Based on the analysis as well as industry best practices, a risk management framework for products is proposed that can assist product managers analyse concepts to ensure adherence to governance requirements. This could assist new product or service offerings in the marketplace do not create a perception of distrust by consumers.
Keywords: Telephone companies -- Risk management -- South Africa; Telephone companies -- South Africa -- Case studies; Telecommunication -- Security measures -- South Africa